ADMINISTRATIVE PRACTICES AND ITS IMPACT ON EMPLOYEE PERFORMANCE: ANALYTICAL STUDY OF THE OPINION OF EMPLOYEES FROM THREE PRIVATE UNIVERSITIES OF ERBIL - Ahmed Talaat Jabbar (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
With recent advances in technology, professionals of all ages are using new tools to enhance productivity, with younger generations often adapting more quickly to new digital trends. As the organization’s job descriptions grow, the expectations of employees increase as well. This research measures the impact of administrative practices on the employee performance. This research is conducted in Erbil, the capital of Iraq's Kurdistan region. Out of the total population of 190 employees, 129 respondents participated in this research; all of whom completed the questionnaire. The sample included teaching as well as non-teaching staff. The data was analyzed through SPSS (Version 24) software. The data was examined using Correlation, ANOVA, & Regression analysis to conclude to fulfill the aims of the research. It was revealed that given the employment and training practices these private universities selected, the result showed that current training and development practices at the private universities were effective and did not require major improvements. Therefore, this administrative approach was identified as the most effective for enhancing staff performance. All examined characteristics of administrative practice were found to considerably and strongly contribute to job performance.